Endoscopic sphincteroplasty: An effective method of extracting bile duct stones by ERCP patients with Billroth II gastrectomy - , Orhan SEZGİN and , Uğur YILMAZ and , Fikret DEMİRCİ and , Burhan ŞAHİN (Turkish Journal of Gastroenterology 1, 2019)
-